Characterizing the Thermal Demands and Mobility Performance During International Wheelchair Rugby Competition - Erica H. Gavel; Erica H. Gavel; Melissa A. Lacroix; Vicky L. Goosey-Tolfrey; Heather M. Logan-Sprenger; Heather M. Logan-Sprenger; Heather M. Logan-Sprenger (Frontiers Media S.A., 2022)
ObjectiveTo determine the thermoregulatory responses and mobility performance of wheelchair rugby (WCR) players during international competition.MethodsEleven male National Team WCR players volunteered for the study. Testing occurred during a four game series against international competition (temp 24.7 ± 0.7°C, relative humidity 50.1 ± 3.6%), with movement time (MT) and gastrointestinal temperature (Tgi) recorded continuously.ResultsThe mean maximal Tgi was 38.6 ± 0.6°C (37.9-39.7) and did not significantly differ among Low-Class, Mid-Class, and High-Class athletes (p > 0.05). Moreover, there was a strong and significant relationship between minutes (min) played per quarter of the game and change in Tgi (r = 0.36, p = 0.01). Athletes moved a total of 27:43 ± 9:40 min:seconds (s), spent a total of 15:02 ± 8.23 min:s in Zone 1 (53.5%), 8:19 ± 3:20 min:s in Zone 2 (31.7%), and 5:59 ± 1:51 min:s in Zone 3 (21.3%). There were no differences among classification in total movement time (p = 0.169) or for speed in Zone 1, Zone 2, or Zone 3 (p > 0.05). The relationship between peak forward speed and total movement time was strong (p = 0.021, r = 0.68).ConclusionThis study demonstrated that the time spent in absolute movement zones is not classification dependent, the change in core temperature is related to movement time per quarter. Furthermore, peak speeds obtained on-court were linked to overall movement time which suggests athletes should warm-up before going on court.